(untitled) (Journal of Architectural Design, 2022)
The article explains the main directions for the restoration and reconstruction of architectural monuments. The experience of local masters in the restoration of monuments in Uzbekistan and Russian scientists who have contributed to the methodology of restoration of architectural monuments is highlighted.